Formation of future foreign language teachers’ research competence in the conditions of a university - Mombekova, М.М. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
Thе article presents an experimental analysis of the formation of research competence of future foreign language teachers. The article discusses the importance of research competence and its formation among students of a pedagogical profile. Acquisition of research competence is the main engine of modernization of modern education in the twenty-first century; therefore, higher education should be oriented towards the formation of vital competencies of future competitive professionals. The article mentioned the strategy “Kazakhstan – 2050”, where its goal is the development of competitive specialists with modern competencies, including research competence. This article reveals the components of research competence, which are a constituent in the formation of research competence of future foreign language teachers. The purpose of the research in this article is the development of future foreign teachers’ research competence in the conditions of a university. The article describes the phased formation of research competence using various pedagogical methods in the conditions of a university. Criteria for evaluating the formation of future foreign language teachers’ research competence in higher educational institutions were determined in the article.
Жоғары оқу орны жағдайында болашақ шетел тілі мұғалімдерінің зерттеу құзыреттілігін қалыптастыру
Формирование исследовательской компетенции у будущих учителей иностранного языка в условиях вуза
Keywords: competence; research competence; motivational-personal component; motivation; theoretical-cognitive component; structural design component; pedagogical methods; formation of research competence